2016
DOI: 10.1163/1568539x-00003362
|View full text |Cite
|
Sign up to set email alerts
|

Work-themed play among young children in foraging and farming communities in Central Africa

Abstract: In small-scale societies children have great access to observing adult roles and this is often reflected in their play, however very few empirical studies of work-themed play have been conducted despite substantial implications that this type of play has for social learning. The current study describes the work-themed play patterns of 1 1/2- to 4-year-old Aka and Bofi foragers and Bofi farmers in Central Africa and examines the extent to which subsistence economy, age, and gender predicted how often children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…M. Endicott and Endicott (2008), Lye (1997), and Vanstone (1965) said that only around the age of 10 do the activities of Batek and Chippewayan boys and girls diverge. For example, Fouts, Bader, and Neitzel (2016) did not find difference in the amount of work-themed play performed by Aka and Bofi boys and girls in early childhood. In middle childhood, both Morelli (1997) studying the Efe and Boyette (2016a) studying the Aka found that boys and girls tend to participate equally in work-themed play or actual chores, while among neighboring farmers, girls were more likely to participate in work than boys.…”
Section: Resultsmentioning
confidence: 78%
“…M. Endicott and Endicott (2008), Lye (1997), and Vanstone (1965) said that only around the age of 10 do the activities of Batek and Chippewayan boys and girls diverge. For example, Fouts, Bader, and Neitzel (2016) did not find difference in the amount of work-themed play performed by Aka and Bofi boys and girls in early childhood. In middle childhood, both Morelli (1997) studying the Efe and Boyette (2016a) studying the Aka found that boys and girls tend to participate equally in work-themed play or actual chores, while among neighboring farmers, girls were more likely to participate in work than boys.…”
Section: Resultsmentioning
confidence: 78%
“…Boyette ( 2013 , 2016 ) and Gallois et al ( 2015 ) found that, as children grow older, they play less and work more, suggesting that play helps them learn subsistence behaviors. In comparing Aka and Bofi foragers with Bofi farmers, Fouts et al ( 2016 ) found that, though Bofi farmer children between the ages of one and four participated in more work-themed play than their foraging counterparts, forager children were in closer proximity to adults and were more likely to use objects when performing work-themed play. Parental beliefs may contribute to cultural beliefs with regard to play; Neuwelt-Truntzer ( 1981 ) argued that Aka parents believe that if children do not play, they will fail to learn.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, participating in adult activities alongside either adults or other children, such as gathering water or firewood, allows a child to develop the necessary competencies to complete these tasks independently (Gaskins 2000 ; Lancy 2012 ; Rogoff et al 2003 ). Finally, in small-scale societies where adult activities are not segregated from those of children, children have ample opportunities to observe adults and to imitate their behaviors (Fouts et al 2016 ; Gaskins and Paradise 2009 ; Odden and Rochat 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Juveniles learn about animal behaviour and biology well before they start hunting, gaining vicarious experience from hundreds of hours of stories heard around the campfire (low-cost, one-to-many teaching by elders). Child pretend play often mimics adult subsistence tasks, especially when actually performing those tasks would be dangerous or risk resource loss [46,47]. Such play behaviour often transitions into increasing participation in the actual work activity.…”
Section: (B) Human Hunting and Teacher Costsmentioning
confidence: 99%